Characterization of Pneumocystis carinii PHR1, a pH-Regulated Gene Important for Cell Wall Integrity - Kottom, Theodore J. (American Society for Microbiology, 2001)
Pneumocystis carinii remains an important opportunistic fungal pathogen causing life-threatening pneumonia in patients with AIDS and malignancy. Currently, little is known about how the organism adapts to environmental stresses and maintains its cellular integrity. We recently discovered an open reading frame approximately 600 bp downstream of the region coding GSC-1, a gene mediating β-glucan cell wall synthesis in P. carinii. The predicted amino acid sequence of this new gene, termed P. carinii PHR1, exhibited 38% homology to Saccharomyces cerevisiae GAS1, a glycosylphosphatidylinositol-anchored protein essential to maintaining cell wall integrity, and 37% homology to Candida albicans PHR1/PHR2, pH-responsive genes encoding proteins recently implicated in cross-linking β-1,3- and β-1,6-glucans. In view of its homology to these related fungal genes, the pH-dependent expression of P. carinii PHR1 was examined. As in C. albicans, P. carinii PHR1 expression was repressed under acidic conditions but induced at neutral and more alkaline pH. PHR1-related proteins have been implicated in glucan cell wall stability under various environmental conditions. Although difficulties with P. carinii culture and transformation have traditionally limited assessment of gene function in the organism itself, we have successfully used heterologous expression of P. carinii genes in related fungi to address functional correlates of P. carinii-encoded proteins. Therefore, the potential role of P. carinii PHR1 in cell wall integrity was examined by assessing its ability to rescue an S. cerevisiae gas1 mutant with absent endogenous Phr1p-like activity. Interestingly, P. carinii PHR1 DNA successfully restored proliferation of S. cerevisiae gas1 mutants under lethal conditions of cell wall stress. These results indicate that P. carinii PHR1 encodes a protein responsive to environmental pH and capable of mediating fungal cell wall integrity.